Atomic-scale characterization of two-dimensional magnets and their heterostructures - Yuli Huang; Mingyue Sun; Yihe Wang; Andrew Thye Shen Wee; Wei Chen (ChemPhysMater, 2023)
The realization of long-range magnetic ordering in two-dimensional (2D) van der Waals systems significantly expands the scope of the 2D family as well as their possible spin-related phenomena and device applications. The atomically thin nature of 2D materials makes their magnetically ordered states sensitive to local environments, and this necessitates advanced characterization at the atomic scale. Here, we briefly review several representative 2D magnetic systems, namely, iron chalcogenides, chromium chalcogenides, chromium trihalides, and their heterostructures. With powerful scanning-probe microscopy, atomically resolved characterization of their crystalline configurations, electronic structures, and magnetization distributions has been achieved, and novel phenomena such as giant tunneling magnetoresistance and topological superconductivity have been observed. Finally, we discuss the challenges and new perspectives in this flourishing field.